2018
DOI: 10.1093/nar/gky780
|View full text |Cite
|
Sign up to set email alerts
|

Power, false discovery rate and Winner’s Curse in eQTL studies

Abstract: Investigation of the genetic architecture of gene expression traits has aided interpretation of disease and trait-associated genetic variants; however, key aspects of expression quantitative trait loci (eQTL) study design and analysis remain understudied. We used extensive, empirically driven simulations to explore eQTL study design and the performance of various analysis strategies. Across multiple testing correction methods, false discoveries of genes with eQTLs (eGenes) were substantially inflated when fals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 51 publications
(60 reference statements)
0
92
1
Order By: Relevance
“…We used the hierarchical correction method to call significant eQTLs as previously described [69,70]. Firstly, p values of all cis SNPs are adjusted for multiple testing for each gene using Benjamini and Yekutieli (BY) method [71] as the locally adjusted p values.…”
Section: Eqtl Mapping Using Matrix Eqtlmentioning
confidence: 99%
“…We used the hierarchical correction method to call significant eQTLs as previously described [69,70]. Firstly, p values of all cis SNPs are adjusted for multiple testing for each gene using Benjamini and Yekutieli (BY) method [71] as the locally adjusted p values.…”
Section: Eqtl Mapping Using Matrix Eqtlmentioning
confidence: 99%
“…This method was demonstrated to produce a lower FDR and greater true positive rate than the method that applies correction over all association tests. 37 We first used the Benjamini and Yekutieli (BY) procedure 38 to adjust p values for all association tests by each gene. We then pooled the minimum BY-adjusted p value of every tested gene to obtain its best associations.…”
Section: Cis-eqtl Mapping In Nigms and Gtexmentioning
confidence: 99%
“…Third, cis-pQTLs in linkage equilibrium that did not meet the trans-pQTL significance threshold in Sun et al were identified in a step-forward procedure. To identify additional cis-pQTLs we applied a hierarchical multiple testing correction procedure that has been shown to control the false discovery rate at 5% in expression quantitative trait loci (eQTL) studies 72,73 to the pQTL summary statistics from Sun et al 2018 15 . For each aptamer, P-values within each 1MB of any gene encoding the targeted protein or protein complex were first Bonferroni corrected for the number of tests within that cis window(s) to obtain locally corrected P-values.…”
Section: Mendelian Randomisation Analysesmentioning
confidence: 99%